The Role-Playing to Improve Expressive Languange Skills Children Aged 4-5 at Tunas Indah Kindergarten - Midawati Midawati; Nurlinda Nurlinda (Information Technology and Science (ITScience), 2026)
Expressive language ability is a crucial aspect of early childhood development that enables children to articulate thoughts, feelings, and needs to their social environment. This study aims to describe the implementation of role-playing method and its effectiveness in improving expressive language skills of children aged 4–5 years at TK Tunas Indah, Jambi City. The study employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, conducted in two cycles each comprising planning, action, observation, and reflection phases. The subjects were 15 children from Group A at TK Tunas Indah Jambi for the 2024/2025 academic year. Data were collected through observation, documentation, and field notes, and analyzed using data reduction, data display, and conclusion drawing. Results revealed a significant improvement in children's expressive language ability across cycles. In the pre-cycle, 40% of children were categorized as Not Yet Developing (BB), 33% as Beginning to Develop (MB), 20% as Developing as Expected (BSH), and 7% as Developing Very Well (BSB). Following Cycle II, BB dropped to 0%, MB to 13%, BSH rose to 40%, and BSB reached 47%. These findings confirm that the role-playing method effectively stimulates children's active language use, expands vocabulary, builds speaking confidence, and strengthens social interaction. This research provides practical contributions for early childhood educators in designing innovative and engaging language learning activities.